Ruthenium based terpyridine complexes as both luminescent and NLO materials. (15th March 2023) - Cheret, Y.; Szukalski, A.; Haupa, K.A.; Popczyk, A.; Mysliwiec, J.; Sahraoui, B.; El-Ghayoury, A.
Graphical abstract: The investigated Ru-complex represents significant and appealing nonlinear optical features showed as generation of 3ω wavelength (yellow straight line) constituting third harmonic of light generation (THG) signal. The fundamental, infrared laser line is drawn as a red line. In the background, a chemical structures of the considered compounds were presented. Abstract: Currently, a lot of attention is paid to seeking new organic low-molecular chromophores, which can provide efficient optical or nonlinear optical (NLO) response. In the last few decades, the idea of preparing multifunctional ligands and their corresponding metal complexes has become more common. In this contribution we describe the synthesis of a new multifunctional terpyridine ligand L and its corresponding heteroleptic (C1 ) and homoleptic (C2 ) complexes. We have investigated the influence of the ligands on the electron cloud distribution, which is straightforwardly connected with provided spectroscopic features. By using Ru(II) metal cation it was possible to enhance NLO response in the manner of third harmonic of light generation. In addition, we describe the synthesis strategy, full spectroscopic characterization, and other 3rd order nonlinear optical properties, in both liquid and solid states. The experimental data were supported by the DFT calculations. A theoretical model explaining a light-emitting mechanism is thus presented. The bis(terpyridine) ruthenium(II) coordination complexes are valuable candidates for opto-electronic devices, like light modulators or generators.